Respon Pertumbuhan Setek Batang Rosmarinus officinalis L. Terhadap Variasi Media Tanam Dan Konsentrasi Air Kelapa Sebagai Zat Pengatur Tumbuh Alami - Zulfikar Alvin Naufal; Felicitas Deru Dewanti; Sutini Sutini (Wahana-Bio: Jurnal Biologi dan Pembelajarannya, 2023)
Rosemary is one of the aromatic herb plants that is known to challenges in its seed production because the propagation of rosemary still relies on seed germination with low germination rates. To overcome this. This research aims to determine the growth response of rosemary stem cuttings to the application of Plant Growth Regulator (PGR) in the form of coconut water, variations in growing media, and their interaction. The study was conducted using a Completely Randomized Design with the variation of growing media and different concentrations of coconut water PGR solution. The experiment was conducted in a greenhouse, with a total of 15 treatment combinations repeated 3 times. The observed parameters included root length, number of roots, and number of shoots, with observations made every two weeks. The results showed that the combination of coconut water concentration and variation in growing media significantly interacted with the growth parameters, namely root length and number of roots. Additionally, individual factors such as the mixed soil and rice husk charcoal growing medium and 75% coconut water concentration separately had a significant effect on the number of sprouts at 42 and 56 days after planting.